Pembinaan FARMACIL (Farmasis Cilik) di SDN 2 Cakranegara - Candra D. Hamdin; Handa Muliasari (Jurnal Gema Ngabdi, 2019)
The drug is known as a preparation used by humans as a healing medium. The origin of the drug is a toxic compound that can be dangerous when using it. The usage of drugs can be obtained if it is used correctly. Basic knowledge about drugs is very important to know so that the benefits of drugs can be obtained. The Indonesian Pharmacists Association (IAI) has made a simple method to facilitate drug use, by carrying out the national program "DAGUSIBU" which is to Get, Use, Save, Disposed of medicines correctly. Some knowledge about drugs such as preparations (form), dosage, side effects, drug hazards must be known as early as possible. This FARMACIL coaching and cadre program will provide guidance to Primary School Students about basic knowledge of medicine. Coaching is carried out with interesting class mentoring. The basic knowledge curriculum for medicine will be delivered in 8 events for 2 months. After the basic material is delivered, then it is evaluated and then carried out cadre. The formation of Farmacil and farmacil Extracurricular became the main objective of this program. Monitoring of the program will be carried out continuously. The results obtained after the FARMACIL cadre class activities took place were elementary school students had basic knowledge about medicine, the birth of FARMACIL cadres at Cakranegara 2 Elementary School and planning of FARMACIL extracurricular formation